PENGARUH MODEL PELAJARAN TGT DAN TAI TERHADAP HASIL BELAJAR MAHASISWA PGSD UNIPA SURABAYA PADA POKOK BAHASAN KONSEP PENDIDIKAN IPS - Prastyo, Danang (Buana Pendidikan, 2018)
This research aims at knowing the influence of learning models Team Assisted Individualization (TAI) and Team Games Tournament (TGT) toward learning achievement of the students of Elementary Teacher Education (PGSD) Unipa Surabaya on the topics such as concept of social science education. The population of this research is the students of Elementary Teacher Education (PGSD) Unipa Surabaya year 2016. The sample of this research is the students of A class, B class and C class year 2014. This research uses experimental. Design uses Randomized Control Group Pretest-Postest Design. At the same time, the data analysis technique used statistic program SPSS version 16. From the research data analysis it can be seen that is no difference between TAI and TGT model in Social Science lesson to PGSD Student Unipa Surabaya.